If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-3z=2
We simplify the equation to the form, which is simple to understand
5-3z=2
We move all terms containing z to the left and all other terms to the right.
-3z=+2-5
We simplify left and right side of the equation.
-3z=-3
We divide both sides of the equation by -3 to get z.
z=1
| 9(x-4)=9-33 | | -2(3x-3)=4x-9 | | 2-4x=-6 | | 4n-24m= | | 225x+4=0 | | ln(x-1)-ln(2x+3)=1 | | f(x)=6x^2-7x+18 | | 7-3d=-18 | | 12+4m=-9 | | 45=6x-3 | | 9-2p=16 | | lx(x-1)-ln(2x+3)=1 | | 34=2x+3x+9 | | 4x+1.5y=6 | | ln(x-1)-ln(2x+3)=1/2 | | 6+5x-x=42 | | 3(2x+5)-8=1 | | d-38=14 | | -(5X-4Y-7)= | | 132-r=209 | | (5/x-3)+1=(30/x^2-9) | | -4-q=-7 | | d+36=18 | | m-18=54 | | 9+d=15 | | 4-m=9 | | 3+5=2(4x+1)-7 | | 2xm=12 | | 8x-25x=8 | | 4+1/4y=-5 | | -120-5x=0 | | (3/x-1)=(5/x+2) |